Mathematical epidemiological modeling and analysis of monkeypox dynamism with non-pharmaceutical intervention using real data from United Kingdom - Ngungu, Mercy; Addai, Emmanuel; Adeniji, Adejimi; Adam, Umar Muhammad; Oshinubi, Kayode (Frontiers in Public Health, 2023)
In this study, a mathematical model for the dynamics of monkeypox virus transmission with non-pharmaceutical intervention is created, examined, and simulated using actual data. Positiveness, invariance, and boundedness of the solutions are thus examined as fundamental features of mathematical models. The equilibrium points and the prerequisites for their stability are achieved. The basic reproduction number, thus the virus transmission coefficient R_0 is determined and quantitatively used to investigate the global stability of the model's steady state. Further, we consider the sensitivity analysis of the parameters according to R_0. The most sensitive variables that are important for infection control are found using the forwards normalised sensitive index. Data from United Kingdom collected between May and August of 2022 is used which also aids in demonstrating the usefulness and practical application of the model to the spread of the disease in United Kingdom. In addition, under the Caputo-Fabrizio operator, Krassnoselskii's fixed point theorem has been used to analyse the existence and uniqueness of the solutions to our suggested model. The numerical simulations are presented in order to assess the system dynamic behaviour. More vulnerability was seen when the monkeypox virus cases initially appeared recently as a consequence of numerical calculations. We advise the policymakers to consider these elements in order to control monkeypox. Based on the findings, we hypothesised that another control parameter could be the memory index or fractional order.